Synthesis and use of universal sequence probes in fluorogenic multi-strand hybridisation complexes for economical nucleic acid testing. - French, D; Richardson, J; Howard, R; Brown, T; Debenham, P (Elsevier, 2015)
Analysis of nucleic acid amplification products has become the gold standard for applications such as pathogen detection and characterisation of single nucleotide polymorphisms and short tandem repeat sequences. The development of real-time PCR and melting curve analysis using fluorescent probes has simplified nucleic acid analyses. However, the cost of probe synthesis can be prohibitive when developing large panels of tests. We describe an economic two-stage method for probe synthesis, and a new method for nucleic acid sequence analysis which together considerably reduce costs. The analysis method utilises three-strand and four-strand hybridisation complexes for the detection and identification of nucleic acid target sequences by real-time PCR and fluorescence melting.